Real time traceability module for halal logistic transportation using GPS and geofence technique - Mohamad, Maizatul Akma (2016)
The general practice of Halal concept in the logistic process has highlighted a number of doubts on the reliability of the Halal goods in every stage of the process, which one of them is the transportation operations. While undergoing the transportation process, Halal goods have the tendency of being contaminated, loss of track and chain breakage due to lack of real time traceability system to execute the monitoring process. Typically, there are a number of tracking systems that enable one to monitor the movements of a certain product, but all of them are too general and contradicting the rules set out by the shariah law in managing the Halal product. This study presents a merged traceability module of GPS tracking system technology with geofence algorithm, entitled the Halal tracer. The significance of Halal tracer traceability module is that it mainly benefits in providing automatic detection on the spatial activity undergone during the shipment process of the Halal goods. The system is able to identify the possibility of cross contamination by examining the vehicle stoppage via geofence technique. The existing geofence technique was upgraded by integrating spatial, temporal and speed rule in the ray casting algorithm used for this technique. As soon as the vehicle is on the move, the tracker will be stimulated, and the stopping location of the vehicle is being inspected, whether it is within the geofence area or otherwise. User will be notified by receiving an email, while the report current and past track can be viewed via web based visualization interface with Google Map as base map. The verification and simulation report illustrate that the module and improved algorithm has successfully been executed to deliver a report of tracking that is in accordance with the requirements of administering Halal goods. A comparison of performance and result of the geofence technique and Family Locator application, developed by Sygic, was made. A user acceptance test has been implemented and most of the respondents agreed that this module will benefit the Halal logistic provider in providing data on real time traceability. Due to its significant function, whereby a conversion of manual procedure into a web based module is necessary, this module will be effective and brings benefits to the authorities, Halal logistic service providers and also users.